Project coordination success factors in European Union-funded research, development and innovation projects under the Horizon 2020 and Horizon Europe programmes - Anna Tenhunen-Lunkka; Riitta Honkanen (Journal of Innovation and Entrepreneurship, 2024)
Success factors for managing European Union-funded research, development and innovation projects is rather uncharted territory and scarce publications exist, even though considering that the H2020 funding was nearly exteuro80 billion, and Horizon Europe is exteuro95,5 billion. Managing these types of projects has been referred to as 'managing the unmanageable', which indicates importance of our study. The aim of this study was to gather input via survey from both project coordinators and partners by assessing factors in five categories of good practices, skills, characteristics and tools of project management, and coordination for successful project implementation. A total of 118 persons replied to the survey who have experience from Horizon 2020 or Horizon Europe funded project(s). Over 80 factors were assessed and rated by the participants. Via standard statistical analysis, a top three lists were created for the different categories from both project partners and coordinators perspectives. A combination of 15 top success factors was formed. Furthermore, to emphasise the practicality of the results, an overarching framework was formed where we propose three prioritised key success factors that research, development, and innovation project management of should focus on. The three key success factors are communication, trust, and collaboration. Communication and trust are further traced down to the coordinator and consortium levels. Active communication and good listening skills are key. Mutual trust is built through high motivation, competence, and active approach to dedicated project activities and roles. Efficient collaboration is reached by nourishing inclusivity and culture, creating a productive environment, and good administrative practices.
Keywords: 650; EU projects; Innovation management; Project management; RDI; RDI management; Success factors